A Weighted Evidence Combination Method Based on Improved Conflict Measure Factor - Xiaochen Xing; Yuanwen Cai; Zhengyu Zhao; Long Cheng; Yan Li (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
D-S evidence theory is usually used for the fusion of multi-source information. But the fusion result is always against with general knowledge for the heavy conflict of evidence. Research on combination of conflict evidence at home and abroad is summarized and analyzed in detail. On the base of this, the conclusion that modified evidence combination method of conflict evidence is more useful can be dawn. Effective evidence conflict measure is the first step of conflict evidence combination. The existing conflict measure methods are summarized and the main problem of those methods is analyzed in detail. Based on previous research of conflict evidence combination, a modified measure factor of evidence conflict which is called Mconf is put forward. Mconf is mainly built up with modified distance of evidence named mdBPA and traditional evidence conflict factor named k. The examples in this paper show that Mconf can measure the evidence conflict correctly, both for general evidence and conflict evidence. DOI: http://dx.doi.org/10.11591/telkomnika.v14i3.7850